Serum Biochemical Parameters in the Ring-Necked Pheasant (Phasianus colchicus) on Breeding Season - Schmidt, Elizabeth Moreira dos Santos; Paulillo, Antonio Carlos; Dittrich, Rosangela Locatelli; Santin, Elizabeth; Beltrame, Olair; Moura, Joelma; de Oliveira, Edson Goncalves (International Journal of Poultry Science, 2007)
The influence of sex on serum biochemical parameters was investigated in adult (52 week-old) ring-necked pheasants on reproductive activity. Statistical comparisons were made for differences in values between male and female birds. Adult females had higher values for serum total protein and albumin. Significant variations were not observed in the analyses in relation to the sex of the birds for urea, uric acid, ratio urea/uric acid and globulins. This study also aimed to determine serum biochemical values for adult ring-necked pheasants.